2015
DOI: 10.1002/jbt.21738
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts Disruption Increases Ochratoxin A Cytotoxicity to Hepatocytes

Abstract: Lipid rafts are microdomains in plasma membrane and can mediate cytotoxicity. In this study, the role of lipid rafts in ochratoxin A-induced toxicity was investigated using Hepatoblastoma Cell Line HepG-2 cells. Disruption of cholesterol-containing lipid rafts enhanced Ochratoxin A (OTA) toxicity, as shown by increased lactate dehydrogenase leakage, increased reactive oxygen species level and reduction of superoxide dismutase activity in a time-dependent manner. Isobaric tags for relative and absolute quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…We next evaluated the presence of oxidative stress by measuring the levels of urinary isoprostanes 42 in β‐MCD‐treated mice and found that the urinary levels were increased compared with control (vehicle‐ and α‐MCD‐treated) mice (Figure 7A). Disruption of lipid rafts and lipid raft clustering are associated with oxidative stress in glomerular epithelial cells and hepatocytes 43‐45 but not breast cancer cells. β‐MCD facilitates the hepatoxicity of ochratoxin 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next evaluated the presence of oxidative stress by measuring the levels of urinary isoprostanes 42 in β‐MCD‐treated mice and found that the urinary levels were increased compared with control (vehicle‐ and α‐MCD‐treated) mice (Figure 7A). Disruption of lipid rafts and lipid raft clustering are associated with oxidative stress in glomerular epithelial cells and hepatocytes 43‐45 but not breast cancer cells. β‐MCD facilitates the hepatoxicity of ochratoxin 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of lipid rafts and lipid raft clustering are associated with oxidative stress in glomerular epithelial cells and hepatocytes 43‐45 but not breast cancer cells. β‐MCD facilitates the hepatoxicity of ochratoxin 45 . Therefore, we further explored the role of lipid raft residency of D 1 R on oxidative stress in mouse RPTCs and found that β‐MCD treatment doubled the production of ROS in the treated cells, indicating the presence of heightened oxidative stress when the lipid rafts were perturbed (Figure 7B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Other study investigated the effect of OTA in the composition of the hepatoblastoma cell line HepG-2 plasma membrane [87]. This showed that OTA induced a loss of more than 85% of hepatotoxicity [87].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Other study investigated the effect of OTA in the composition of the hepatoblastoma cell line HepG-2 plasma membrane [87]. This showed that OTA induced a loss of more than 85% of hepatotoxicity [87]. HepG2 cells were originally derived from a male patient's liver, and so the same results in liver cells derived from a female patient remain to be confirmed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Due to its chemical stability during food and feed processing, OTA may reside in foodstuff, spices and animal feed [ 8 , 9 , 10 , 11 ]. In addition, OTA is a nephrotoxic toxin [ 12 ] with strong carcinogenic effects on rodents [ 13 ]. OTA has been proven to be teratogenic, embryotoxic, genotoxic, neurotoxic and immunosuppressive [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%